Peran Organisasi Profesi Guru di SMP PGRI 7 Balikpapan - Nurmayanti, Erica; Dwi Handayani, Fitri; Indriawati, Prita (Jurnal Syntax Fusion, 2023)
The teacher professional organization is a forum whose role is to oversee and deal with issues related to education and work together to overcome them. As an organization, the Teacher Professional Organization has a system to maintain harmony at all times. This study was written to explore how the role of professional teacher organizations plays a role in teacher survival. The object of research is SMP PGRI 7 Balikpapan teachers, using interview and observation data collection methods. The results of the study obtained the results of external factors that positively helped the survival of the teaching profession, namely the need for teachers who continued to increase and the government had a positive will to improve education. While positive internal teacher factors support the survival and development of the teaching profession, namely people who will and have become teachers, teacher organizations, and the availability of teacher education facilities.